2014
DOI: 10.1002/2013gb004678
|View full text |Cite
|
Sign up to set email alerts
|

Variability of alkalinity and the alkalinity‐salinity relationship in the tropical and subtropical surface ocean

Abstract: The variability of total alkalinity (TA) and its relationship with salinity in the tropical and subtropical surface ocean were examined using data collected in various marine environments from a ship of opportunity. In the open ocean regions of the Atlantic, Pacific, and Indian Oceans, sea surface TA variability was observed to be mainly controlled by the simple dilution or concentration (SDC) effect of precipitation and evaporation, and the measured concentrations of TA agreed well with those predicted from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 60 publications
4
50
1
Order By: Relevance
“…In the Mediterranean Sea, several studies have shown that the relationship between A T and S is linear (Copin-Montégut, 1993;Copin-Montégut and Bégovic, 2002;Hassoun et al, 2015b;Jiang et al, 2014;Rivaro et al, 2010;. In other studies, the sea surface temperature (T ) has been included as an additional proxy for changes in surface water A T related to convective mixing (Lee et al, 2006;Touratier and Goyet, 2011).…”
Section: Fitting a T In The Mediterranean Sea Surface Watersmentioning
confidence: 99%
“…In the Mediterranean Sea, several studies have shown that the relationship between A T and S is linear (Copin-Montégut, 1993;Copin-Montégut and Bégovic, 2002;Hassoun et al, 2015b;Jiang et al, 2014;Rivaro et al, 2010;. In other studies, the sea surface temperature (T ) has been included as an additional proxy for changes in surface water A T related to convective mixing (Lee et al, 2006;Touratier and Goyet, 2011).…”
Section: Fitting a T In The Mediterranean Sea Surface Watersmentioning
confidence: 99%
“…Waters with higher TA are less prone to rapid change in ocean pH and may provide refuge for marine biodiversity in the face of OA. TA is conservatively related to salinity due to convective mixing and the addition or removal of freshwater to a water 30 mass (Cai et al, 2010;Jiang et al, 2014;Lee et al, 2006;Millero et al, 1998). This relationship has been exploited to predict alkalinity at the global scale from historical databases of ocean salinity (Lee et al, 2006;Millero et al, 1998).…”
mentioning
confidence: 99%
“…To address this limitation, additional proxy variables have been incorporated into predictive alkalinity models to account for processes that affect TA non-conservatively (Jiang et al, 2014). For example, seawater temperature 40…”
mentioning
confidence: 99%
See 2 more Smart Citations